You are what you eat: O-linked N-acetylglucosamine in disease, development and epigenetics. Issue 4 (July 2015) - Olivier-Van Stichelen, Stéphanie; Hanover, John A.
Abstract : Purpose of review: The O- linked N-acetylglucosamine (O-GlcNAc) modification is both responsive to nutrient availability and capable of altering intracellular cellular signalling. We summarize data defining a role for O- GlcNAcylation in metabolic homeostasis and epigenetic regulation of development in the intrauterine environment. Recent findings: O- GlcNAc transferase (OGT) catalyzes nutrient-driven O- GlcNAc addition and is subject to random X-inactivation. OGT plays key roles in growth factor signalling, stem cell biology, epigenetics and possibly imprinting. The O- GlcNAcase, which removes O- GlcNAc, is subject to tight regulation by higher order chromatin structure. O- GlcNAc cycling plays an important role in the intrauterine environment wherein OGT expression is an important biomarker of placental stress. Summary: Regulation of O- GlcNAc cycling by X-inactivation, epigenetic regulation and nutrient-driven processes makes it an ideal candidate for a nutrient-dependent epigenetic regulator of human disease. In addition, O- GlcNAc cycling influences chromatin modifiers critical to the regulation and timing of normal development including the polycomb repression complex and the ten-eleven translocation proteins mediating DNA methyl cytosine demethylation. The pathway also impacts the hypothalamic-pituitary-adrenal axis critical to intrauterine programming influencing disease susceptibility in later life.